An open-label, single-arm trial of cryoneurolysis for improvements in pain, Activities of Daily Living and Quality of Life in patients with symptomatic ankle osteoarthritis - Perry, TA; Segal, NA (Elsevier, 2022)
Objective Cryoneurolysis, cold-induced reversible conduction block of peripheral nerves, is an effective treatment for reducing knee osteoarthritis (OA) symptoms and opioid use following knee arthroplasty. There are limited data concerning its use for ankle OA. Our aim was to assess clinically significant long-term symptomatic relief of ankle OA with cryoneurolysis.